Higher education in exceptional situations and the imprint of technology - Telmo Mendoza Mera, Jean; Rodríguez Gámez, María; María San Andrés Laz, Esthela (International Journal of Psychosocial Rehabilitation, 2020)
-The Ecuadorian Constitution recognizes education as a public function of the first order due to the impact It represents for the development of the Country, so guaranteeing its continuity and quality is a priority task for the State. The objective of the work is to carry out a critical scientific-based analysis, related to the continuity of substantive functions in higher education, under exceptional conditions derived from the impact of COVID 19, evaluating the possibilities offered by virtual technologies for its execution. A review result is presented where articles, books, brochures, institutional reports and other documents were analyzed, for which there search method was used Desh Research, which involves the use of existing information, which is collected, analyzed and summarized to increase the general effectiveness of the research, produce critical analyzes and reach precise conclusions on the subject studied. We take advantage of the data derived from a survey of professors and students at a university on the Ecuadorian coast, related to the management of virtual technologies, platforms and tools in the educational process. It is expected that the critical analysis that is addressed in the work will serve as a theoretical reference for university managers and professors in general, to guarantee the required material assurance and an adequate organization in the development of the different modalities that virtual education contemplates, for the fulfillment of the substantive functions of Ecuadorian universities.